Biomass as Feedstock in the Chemical Industry – An Examination from an Exergetic Point of View. Issue 2 (7th January 2013) - Frenzel, P.; Fayyaz, S.; Hillerbrand, R.; Pfennig, A.
Abstract Crude oil is the most important raw material for the chemical industry. Due to the continually rising price of crude oil, alternative carbon sources are becoming increasingly important. Biomass is basically the only available renewable carbon source. Because the chemical composition of biomass differs from fossil raw materials, the raw‐material change also offers many chances for new product properties and applications. At the same time, the chemical processes have to be redesigned if the feedstock changes to biomass. Here, the effects of a raw‐material change are examined on a rather generic level. The study is based on exergy balances and indicates that it is exergetically advisable to reconsider the previously established system of platform and basic chemicals. In general, exergy losses can be minimized if the synthesis pathways leading to the final products are adapted to the chemical structure of biomass.